2004
DOI: 10.1002/jemt.20046
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen autophagy

Abstract: Glycogen autophagy, which includes the sequestration and degradation of cell glycogen in the autophagic vacuoles, is a selective process under conditions of demand for the massive hepatic production of glucose, as in the postnatal period. It represents a link between autophagy and glycogen metabolism. The formation of autophagic vacuoles in the hepatocytes of newborn animals is spatially and biochemically related to the degradation of cell glycogen. Many molecular elements and signaling pathways including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 143 publications
(180 reference statements)
3
61
0
1
Order By: Relevance
“…Hypoglycemia has long been thought to induce lysosomal degradation of glycogen in liver in the immediate postnatal period of starvation. 39,40 On the other hand, the neonatal pattern of starvation-induced autophagy does not include liver, 38 and the role for hepatic glycogen autophagy in the early postnatal period has been challenged by data from autophagy deficient mice: neonates appear to depend on the amino acids produced by autophagy rather than on glucose supply for energy homeostasis and survival. 37 In this study, undifferentiated human myoblasts, multinucleated myotubes, and muscle fibers showed very different levels of basal autophagic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia has long been thought to induce lysosomal degradation of glycogen in liver in the immediate postnatal period of starvation. 39,40 On the other hand, the neonatal pattern of starvation-induced autophagy does not include liver, 38 and the role for hepatic glycogen autophagy in the early postnatal period has been challenged by data from autophagy deficient mice: neonates appear to depend on the amino acids produced by autophagy rather than on glucose supply for energy homeostasis and survival. 37 In this study, undifferentiated human myoblasts, multinucleated myotubes, and muscle fibers showed very different levels of basal autophagic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Atg5-deficient mice have increased AMPK activation in the heart, suggesting a shortage in ATP production. 51 However, gluconeogenic mechanisms are not fully established in the newborn, 53 and they may need a direct supply of glucose. Degradation of glycogen could meet this demand.…”
Section: Effect Of Energy Level and Ampk In Autophagy Induction In Hementioning
confidence: 99%
“…Autophagic degradation of glycogen in the newborn liver has long been recognized as an important survival mechanism for the newborn to adapt to the postnatal environment. 53 Glycogen autophagy is likely stimulated by glucagon, which is secreted in response to hypoglycemia normally occurring in the newborn. In newborn hepatocytes, most of the autophagosomes are spatially and functionally related to glycogen, appearing at the borders of glycogen stores and usually containing various amounts of glycogen.…”
Section: Effect Of Energy Level and Ampk In Autophagy Induction In Hementioning
confidence: 99%
See 1 more Smart Citation
“…49 In the newborn also, provision of glucose by glycogen degradation is an important role of autophagy until provision of nutrients by milk takes place. 50 …”
Section: Autophagy In Maintenance Of Homeostasis In Liver and Hepaticmentioning
confidence: 99%